Morfoanatomi, Berat Basah Kotiledon dan Ketebalan Daun Kecambah Kacang Hijau (Phaseolus vulgaris L.) pada Naungan yang Berbeda - Haryanti, Sri; Budihastuti, Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
The Â functions of cotyledons are to do photosynthesis during the epigeal growth Â to absorb, and to transport nutrients from endosperm to the growing sprouts. The morphology and the anatomy changes of cotyledons prior to the blooming of the first leaf showed that physiologis changes occured inside them. The aims of this research are to find out the morpho anatomy of cotyledons and the growth of the leaves during sprouting phase of green peanut sprouts applied in three different environments. This research was conducted in the structural and functional Biology Laboratory in FSM undip dated May 2014-july 2014. The research design was CRD (CompletelyRandomisedDesign) and the data were analyzed using ANOVA which has 95% validity. This research applied three different treatments were Dark (D), Medium (M), Bright (B) three times. The parameters observed were the morpho anatomy, the wet weight of cotyledons, and the leaf thickness of green peanut sprouts in three different environments. The research showed that the morphology and the anatomy of cotyledons were descriptively different on day 4 and day 8, not only in parekim cells of each group but also in the chlorophyl level and the amylum inside them. The wet weight of cotyledons and the leaf thickness were extremely different too when the sprouts aged 8 days. Â Keywords : morphoanatomy, wet weight, cotyledon, environments